The self and memory - Beike, Denise R.; Lampinen, James M.; Behrend, Douglas A. (Studies in self and identity series., 2004)
How we think of ourselves depends largely on what we remember from our lives, and what we remember is biased in many ways by how we think of ourselves. The complex interplay of the self and memory is the topic of this volume.